The Effect of Using Concept Check Questions on Iranian Female EFL Learners’ Grammar - Yalda Kargar; Hoda Divsar (International Journal of English Language and Translation Studies, 2019)
The present study examined the effect of concept check questions on Iranian female EFL learners' grammar. To achieve this end, 40 students were selected based on random sampling and were homogenized based on the results of OPT. The participants then were randomly assigned as the experimental and control groups. The grammar topics were taught using concept check questions in the experimental group and the control group received placebo in the form of traditional teaching without the use of concept check questions. In order to measure the participants' grammatical proficiency, IELTS-based grammar tests were administered as the pre-test and the post-test. The independent sample t-test was run in order to find out if there were any significant differences between the control and experimental groups in terms of their grammar knowledge at the beginning and at the end of the study. Moreover, paired t-tests were run to measure the students' possible progression within each groups. It was concluded that the use of the concept check questions was advantageous in enhancing EFL learners‟ grammar. This study has pedagogical implications for EFL teachers manipulate the use of concept check questions as an alternative strategy when traditional way of teaching grammar do not lead to the effective learning.